Intellectual capitals, business models and performance measurements in forming strategic network. (1st July 2011) - Peng, Tzu-Ju Ann; Yang, Johnson Chung-Hsin; Pike, Stephen; Roos, Göran
How firms identify the intellectual capitals, business models and performance measurements for forming a strategic network with competitors? Both intellectual capital and coopetition strategy have become heated issues in strategic management field. Firms involved in cooperation with competitors should not only design their collective business models but also dedicate their intellectual capitals to create performance. Linking intellectual capital perspective, business model, and performance management, this paper aims at answering three questions: What are the intellectual capitals required to form a strategic network with competitors? What is the collective business models designed for cooperative strategies? And what are the performance indicators for measuring the collective business models? In this study, we have investigated a supermarket strategic network. We conducted an in-depth face-to-face interview with 14 CEOs in the network. They, together, have defined five key business models and developed important intellectual capitals necessary for implementation of the business models. They also have identified critical performance measurements. This practice-oriented study contributes a more complete understanding of intellectual capital, business model, and performance measurement in forming strategic network.